2023
DOI: 10.3390/biom13060879
|View full text |Cite
|
Sign up to set email alerts
|

Functional Expression of IP, 5-HT4, D1, A2A, and VIP Receptors in Human Odontoblast Cell Line

Eri Kitayama,
Maki Kimura,
Takehito Ouchi
et al.

Abstract: Odontoblasts are involved in sensory generation as sensory receptor cells and in dentin formation. We previously reported that an increase in intracellular cAMP levels by cannabinoid 1 receptor activation induces Ca2+ influx via transient receptor potential vanilloid subfamily member 1 channels in odontoblasts, indicating that intracellular cAMP/Ca2+ signal coupling is involved in dentinal pain generation and reactionary dentin formation. Here, intracellular cAMP dynamics in cultured human odontoblasts were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 60 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…This increase was inhibited by using an adenylyl cyclase inhibitor and the abovementioned receptor antagonists in a dose-dependent manner. These results suggest that odontoblasts functionally express the G s -protein-coupled IP, 5-HT4, D1, A2A, and VIP receptors [15].…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…This increase was inhibited by using an adenylyl cyclase inhibitor and the abovementioned receptor antagonists in a dose-dependent manner. These results suggest that odontoblasts functionally express the G s -protein-coupled IP, 5-HT4, D1, A2A, and VIP receptors [15].…”
mentioning
confidence: 72%
“…Kitayama et al reported that in the presence of plasma membrane Gα s , prostaglandin I2 (IP), 5-hydroxytryptamine 5-HT4 (5-HT4), dopamine D1 (D1), adenosine A2A (A2A), and vasoactive intestinal polypeptide (VIP) receptors, immunoreactivity was observed in human odontoblasts [15]. Furthermore, in the presence of extracellular Ca 2+ , the application of IP, 5-HT4, D1, A2A, and VIP receptor agonists increased intracellular cAMP levels.…”
mentioning
confidence: 99%